Ethics in Islam: a critical survey - Mohd Nasir Omar (Penerbit Universiti Kebangsaan Malaysia, 2010)
In Islam, ethics (akhlaq) is inseparable from religion and is built entirely upon it. Naturally, therefore, the Qur’an and the Sunnah are the ultimate sources for Muslim ethics. The books on adab (good manners) and makarim alakhlaq (noble qualities of character), which have embodied the earliest works on ethics in Islam demonstrate the extant to which they utilize the Qur’an and the Sunnah. However, early Muslim discussions on ethical philosophy, such as those by al-Kindi (d. 874), al-Farabi (d. 950) and Ibn Sina (d. 1037), did not attain to the status of a discipline though invariably serving as an introduction to their wider studies on politics, law and other fields of knowledge. Miskawayh (d.1030), through his famous ethical work on ethics, Tahdhib al-Akhlaq, was the first Muslim moralist to have separated ethics from other disciplines, offering a very thorough analytical system of Islamic ethics. Thus, this qualitative study which applies conceptual content analysis method seeks to make a critical survey of the development of ethical thought in Islam.